Glucosylation of smoke-derived volatiles in grapevine (vitis vinifera) is catalyzed by a promiscuous resveratrol/guaiacol glucosyltransferase - Haratl, Katja; Huang, Fong-Chin; Giri, Ashok P.; Franz-Oberdorf, Katrin; Frotscher, Johanna; Shao, Yang; Hoffmann, Thomas; Schwab, Wilfried (Journal of Agricultural and Food Chemistry, 2017)
Vinification of grapes (Vitis vinifera) exposed to forest fire smoke can yield unpalatable wine due to the presence of taint compounds from smoke and the release of smoke derived volatiles from their respective glycosides during the fermentation process or in-mouth during consumption. To identify glycosyltransferases (GTs) involved in the formation of glycosidically bound smoke-derived volatiles we performed gene expression analysis of candidate GTs in different grapevine tissues. Second, substrates derived from bushfire smoke or naturally occurring in grapes were screened with the candidate recombinant GTs. A resveratrol GT (UGT72B27) gene, highly expressed in grapevine leaves and berries was identified to be responsible for the production of the phenolic glucosides. UGT72B27 converted the stilbene trans-resveratrol mainly to the 3-O-glucoside. Kinetic analyses yielded specificity constants (k(cat)/K-m) of 114, 17, 9, 8, and 2 mM(-1) s(-1) for guaiacol, trans-resveratrol, syringol, methylsyringol, and methylguaiacol, respectively. This knowledge will help to design strategies for managing the risk of producing smoke-affected wines.

Structural and functional analysis of UGT92G6 suggests an evolutionary link between mono- and disaccharide glycoside-forming transferases - Huang, Fong-Chin; Giri, Ashok; Daniilidis, Melina; Sun, Guangxin; Härtl, Katja; Hoffmann, Thomas; Schwab, Wilfried (Plant and Cell Physiology, 2018)
Glycosylation mediated by UDP-dependent glycosyltransferase (UGT) is one of the most common reactions for the biosynthesis of small molecule glycosides. As glycosides have various biological roles, we characterized UGT genes from grapevine (Vitis vinifera). In silico analysis of VvUGT genes that were highly expressed in leaves identified UGT92G6 which showed sequence similarity to both monosaccharide and disaccharide glucoside-forming transferases. The recombinant UGT92G6 glucosylated phenolics, among them caffeic acid, carvacrol, eugenol and raspberry ketone, and also accepted geranyl glucoside and citronellyl glucoside. Thus, UGT92G6 formed mono- and diglucosides in vitro from distinct compounds. The enzyme specificity constant Vmax/Km ratios indicated that UGT92G6 exhibited the highest specificity towards caffeic acid, producing almost equal amounts of the 3- and 4-O-glucoside. Transient overexpression of UGT92G6 in Nicotiana benthamiana leaves confirmed the production of caffeoyl glucoside; however, the level of geranyl diglucoside was not elevated upon overexpression of UGT92G6, even after co-expression of genes encoding geraniol synthase and geraniol UGT to provide sufficient precursor. Comparative sequence and 3-D structure analysis identified a sequence motif characteristic for monoglucoside-forming UGTs in UGT92G6, suggesting an evolutionary link between mono- and disaccharide glycoside UGTs. Thus, UGT92G6 functions as a mono- and diglucosyltransferase in vitro, but acts as a caffeoyl glucoside UGT in N. benthamiana.